The level of depression and perceived social support in parents of children treated for cancer - Burkiewicz, Anna; Samardakiewicz, Marzena; Karczmarczyk, Tomasz (Psychoonkologia, 2017)
Introduction : The diagnosis of cancer in a child affects the entire family. Parents of ill children are particularly vulnerable to negative emotions and psychological disorders. The aim of the study was to assess the level of depression and perceived social support among parents of children treated for cancer. Material and methods : The study group consisted of 50 parents of children diagnosed with cancer. Data were collected using a survey form, the Beck Depression Inventory (BDI) and the Social Support Rating Scale (ISEL-40 v. GP). Results and conclusions : In the group of parents the average score on the BDI was 18 points (SD = 8, p > 0.05). In most subjects experienced at least symptoms classified as mild depression (68%) and in a substantial part of their symptoms of moderate (16%) and severe (16%) depression. In this trial achieved a statistically significant correlation between depression level and the results of each subscales in the Social Support Rating Scale. The highest, moderate correlation was obtained between depressiveness and self-esteem subscale (r = –0.4717, p = 0.001). The results show the usefulness of screening tools, such as the BDI and Social Support Rating Scale in recognition of the risk of depression in parents and identifying their deficits in social support.